Mother to Infant Transmission of Hepatitis B Virus in the Face of Neonatal Immunization Is Not Necessarily Primary Vaccine Failure. (12th July 2021) - Ijaz, Samreen; Derrick, Jade; Shute, Justin; Ireland, Georgina; Hayden, Iain; Ngui, Siew Lin; Mandal, Sema; Tedder, Richard S
Abstract: Background: Surveillance programs undertaken in infants born to mothers with hepatitis B virus (HBV) provide an opportunity to analyze virological markers from the neonate and early infancy. These data inform on mechanisms of HBV transmission and how available interventions can be better used for control of HBV infections arising at the mother/child interface. Methods: Retrospective analysis of HBV serological markers was undertaken in dried blood spots collected from infants born to mothers infected with HBV. In addition, molecular analysis was performed in newborn blood spot cards, collected after birth, from infants identified as infected with HBV despite receiving prophylaxis. Results: Perinatal exposure could not account for all transmissions, with at least one-quarter (22%) of infants already infected in utero. All harbored a wild-type hepatitis B surface antigen (HBsAg), with identical sequences noted in the neonatal and early infancy samples. In contrast, in infants infected perinatally (43%), selection of viruses harboring amino acid changes in the HBsAg were common (80% of sequences) and divergent from the linked maternal sample. Conclusion: Currently considered to represent vaccine failure, it is likely that a proportion of HBV infections result from in utero acquisition. These infections are unlikely to be susceptible to postnatal prophylaxis, and current recommendations for maternal antiviral treatment may be too late to prevent transmission. Consideration should be given to the earlier use of antivirals during gestation to reduce the risk of intrauterine transmission together with completion of the immunization schedule also to reduce the perinatal risk of HBV transmission. Abstract : Analysis of virological markers from the neonate and early infancy indicates there are multiple mechanisms associated with HBV transmission from mother to infant. Better utilization of currently available interventions should be considered to reduce further HBV transmission.